2018 IEEE 23rd Pacific Rim International Symposium on Dependable Computing (PRDC) 2018
DOI: 10.1109/prdc.2018.00037
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Data Error Detection Technique for Dependable Embedded Software

Abstract: This paper presents a new software-implemented data error detection technique called Full Duplication and Selective Comparison. Our technique combines the ideas of existing techniques in order to increase the fault detection ratio, decrease the imposed code size and execution time overhead. As the name gives away, we opt to duplicate the entire code base and place comparison instructions in critical basic blocks only. The critical basic blocks are the blocks with two or more incoming edges. We evaluate our tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Being one of the best known DFED techniques, it is well suited to analyze DETECTOR's DFE detection capability. Based on this technique, Thati et al developed FDSC, which generally showed an improved error detection ratio [23]. Combined, SWIFT and FDSC are well suited to evaluate the DFE detection capability of DETECTOR in light of the state-of-the-art.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being one of the best known DFED techniques, it is well suited to analyze DETECTOR's DFE detection capability. Based on this technique, Thati et al developed FDSC, which generally showed an improved error detection ratio [23]. Combined, SWIFT and FDSC are well suited to evaluate the DFE detection capability of DETECTOR in light of the state-of-the-art.…”
Section: Resultsmentioning
confidence: 99%
“…In the comparison stage, each used register is compared to its matching shadow register to make sure the data is still correct. Over the years, many techniques using different comparison and duplication strategies have been developed [20]- [23]. Thati et al performed several studies showing how the choice of duplication and comparison strategy, and according trade-off with imposed overhead, affects the error detection capability of those techniques [24].…”
Section: Related Workmentioning
confidence: 99%
“…For DFE detection, our techniques are compared to both SWIFT (Software Implemented Fault Tolerance), introduced by Reis et al [21], and FDSC (Full Duplication Selective Comparison), introduced by Thati et al [16]. Both use the duplication and comparison strategy to detect DFEs.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Using the developed HIL setup, bit-flips can be injected in the remaining cpu registers to cause data flow errors risk free. Similarly, the effectiveness of data flow error detection techniques can be evaluated when applied to a more input/output-driven case study [4,17]. Once known, the best performing data flow error detection technique can be combined with RACFED to develop a technique that is able to detect both control flow errors and data flow errors.…”
Section: Drawback Of the Created Fault Injection Setupmentioning
confidence: 99%